2018
DOI: 10.1039/c8tb02310g
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine nanostructures as biomaterials for medical applications

Abstract: Recent advances in polydopamine synthesis are described with a particular focus on biomedical applications. Prospects and future challenges for the application of polydopamine as a biomaterial are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…Of particular interest is polydopamine (PDA), a coating material that has many appealing characteristics such as the ability to coat most inorganic and organic materials, low toxicity, one-step deposition using a simple method, and multiple functional properties 1 3 . Hence, since its inception in 2007, its utilization has grown extensively in numerous fields of engineering, including biomaterials 4 , 5 , energy storage and harvesting devices 6 , photonics 7 , 8 , and medical therapeutics 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is polydopamine (PDA), a coating material that has many appealing characteristics such as the ability to coat most inorganic and organic materials, low toxicity, one-step deposition using a simple method, and multiple functional properties 1 3 . Hence, since its inception in 2007, its utilization has grown extensively in numerous fields of engineering, including biomaterials 4 , 5 , energy storage and harvesting devices 6 , photonics 7 , 8 , and medical therapeutics 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 54 , 55 Produced by the self-polymerization of dopamine, PDA contains catechol and amine groups and presents a chemical composition analogous to that of the mussel adhesive proteins. 56 , 57 Due to its unique chemistry and the interesting assortment of reactive functional groups, this bioinspired coating can act as a compatibilizer in multiple filler/matrix systems and can be subsequently functionalized. 54 , 58 PDA has been proven to be effective in improving the filler–matrix adhesion with several types of fillers (e.g., nanoclays, 59 carbon nanotubes 60 ), but a very limited number of articles can be found on the application of this coating procedure to formaldehyde-based resins and, to the best of the authors’ knowledge, no articles have been published on the coating of PCM microcapsules with PDA.…”
Section: Introductionmentioning
confidence: 99%
“…We consistently found modest, yet statistically significant, reductions in cell numbers for each of the PDA-functionalised TCP wells compared to untreated controls ( Figure 1A). The reduction in cell number was approximately 11% (p = 0.01) for PDA films formed over 24 h. A further reduction at around 16% (p < 0.001) occurred for cells exposed to PDA films generated over 48 and 72 h. Extended DHC exposure times generate thick PDA films with greater roughness [27], a feature that can have a negative effect on cell attachment and growth [28]. We subsequently found that TCP wells treated for two hours with DHC resulted in the development of PDA films that were completely compatible with MG63 viability ( Figure 1B).…”
Section: Short-term Development Of Pda Films Are Compatible With Ostementioning
confidence: 90%